Implementasi Clustered Container Dengan Docker Sarm - Suci Nurlita Putri Suci; Muhammad Arif Fadhly Ridha (Politeknik Caltex Riau, 2021)
Rapid technological developments can encourage jobs in all fields. Technology is created based on ever-increasing needs and resources. However, the problem that often occurs is that high traffic causes the server to go down because the server is still using conventional computing, so that the server workload becomes heavy and overloaded. By using cluster computing technology, incoming processes can be distributed evenly among each device or hardware node. As technology advances, clusters can be combined with containers. One of the container technology management platforms is docker. Docker has one of its products, docker swarm, which can deploy containers on multiple hosts. When the server is on standby, conventional technology uses the highest CPU and memory. Where CPU usage is 6.2 ms and memory usage is 29.4%. And when the server is busy, conventional technology uses high amounts of CPU and memory. CPU usage is 4324.1 m/s and memory usage is 45%. So that the test results obtained that swarm technology can lighten the burden of server performance compared to conventional. Keywords: Container, Server, Docker, Swarm, CPU, Memory.